(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Hybrid energy system consists of two or more forms of energy sources. This dissertation presents a control of a micro-grid which is fed by hybrid energy sources. It is fed by wind energy, the conversion of which is done via a setup which has a doubly fed induction generator (DFIG) and a battery bank with a common DC bus. It is also fed by solar energy, the conversion of which is done using a solar photovoltaic (PV) array. The common DC bus is used for evacuating this power via DC-DC boost converter. A vector control of LSC is used for managing the voltage and frequency. The setup works when wind power source is inaccessible. The algorithm for both the energy blocks contains a maximum power point tracking (MPPT). The simulation for the said mode has been developed using MATLAB. A prototype is finally implemented. The study of the said model is then made for various inputs under various load conditions. It is seen that the power quality remains within the satisfactory breaking points at high terminals.